(untitled) (European Bison Conservation Newsletter, 2016)
Summarized is the history of European bison restitution in Russia (formerly Soviet Union) since 1946, and in particular, achievements of Prioksko-Terrasny State Nature Reserve. Described are main assumptions of the program for wisent breeding, proposed by Michael Zablotsky. Listed are recommendations for the future work on securing the survival of the species, and identified are main threats related to its genetic purity.